1999
DOI: 10.1046/j.1469-7580.1999.19430363.x
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of fast myosin heavy chain‐based muscle fibres in the gluteus medius of untrained horses: mismatch between antigenic and ATPase determinants

Abstract: The distribution of muscle fibres classified on the basis of their content of different myosin heavy chain (MHC) isoforms was analysed in muscle biopsies from the gluteus medius of adult untrained horses by correlating immunohistochemistry with specific anti-MHC monoclonal antibodies and standard myofibrillar ATPase (mATPase) histochemistry. Percutaneous needle biopsies were taken at 3 depths (20, 40 and 60 mm) from 4 4-y-old Andalusian stallions. The percentage of ' pure ' I MHC fibres increased where… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
27
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 24 publications
4
27
0
Order By: Relevance
“…Hybrid fibers are usually interpreted as transitory fibers (Pette and Staron 1997). However, because of the regular finding of substantial numbers of especially MyHC type 2ad protein hybrid fibers, these fibers are now more regarded as a "true" type, possibly as a functional intermediate between type 2a and type 2d/x fibers Andersen and Schiaffino 1997;Lefaucheur et al 1998;Andersen et al 1999;Linnane et al 1999;Rivero et al 1999;Stephenson 2001;Dingboom et al 2002). Because at the transcriptional level hardly any hybrid fibers are detected, no functional mRNA intermediate is apparently necessary between the type 2a and type 2d/x fibers.…”
Section: Discussionmentioning
confidence: 99%
“…Hybrid fibers are usually interpreted as transitory fibers (Pette and Staron 1997). However, because of the regular finding of substantial numbers of especially MyHC type 2ad protein hybrid fibers, these fibers are now more regarded as a "true" type, possibly as a functional intermediate between type 2a and type 2d/x fibers Andersen and Schiaffino 1997;Lefaucheur et al 1998;Andersen et al 1999;Linnane et al 1999;Rivero et al 1999;Stephenson 2001;Dingboom et al 2002). Because at the transcriptional level hardly any hybrid fibers are detected, no functional mRNA intermediate is apparently necessary between the type 2a and type 2d/x fibers.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that muscles of the Thoroughbred horse are composed of Type I, Type IIa, and Type IIx fibers (Billeter et al, 1988;Sosnicki et al, 1989;Rivero et al, 1996;Serrano et al, 1996). Furthermore, the development of immunohistochemical techniques has permitted identification of hybrid muscle fibers expressing two types of myosin heavy chain (MHC) isoforms (Linnane et al, 1999;Rivero et al, 1999;Quiroz-Rothe and Rivero, 2001). Although some previous studies, including our study, demonstrated that hybrid fibers (I/ IIa and IIa/x) were detected in the gluteus medius muscle in Thoroughbred horses, the percentages of these fibers decreased to less than 4.9% until they were 24 months old (Yamano et al, 2005).…”
mentioning
confidence: 99%
“…Hence, regulation of hybrid fibers is transcriptionally controlled in the equine gluteus medius muscle. Although hybrid MyHC 2ad protein fibers are regarded as a 'true' type because of their regular appearance, they can also be classified as transitory fibers as suggested by Pette and Staron (1997) and demonstrated in this paper (Andersen et al 1999b;Linnane et al 1999;Rivero et al 1999;Stephenson 2001;Dingboom et al 2002). The appearance of hybrid and mismatched fibers indicates that fiber-type transition occurs in presumably normal skeletal muscles not subjected to any training protocol.…”
Section: Discussionmentioning
confidence: 98%
“…They were taken as deep as possible (until resistance from the iliac wing was reached). Tissue samples were either open (horse A and horse D, 500 mg) or needle (horse B and horse C, 100 mg) biopsies, taken from the same location in the muscle to ensure comparable fiber-type composition (Serrano et al 1996;Linnane et al 1999). Samples were divided into small portions (maximum 50 mg) and rolled in talcum powder, mounted on cork blocks with the use of OCT embedding medium, and oriented so that the fibers could be sectioned either transversely or longitudinally and frozen in liquid nitrogen.…”
Section: Muscle Biopsiesmentioning
confidence: 99%
See 1 more Smart Citation